ANALISIS POTENSI EKONOMI DAN PEMASARAN PRODUK PERIKANAN TANGKAP DI ZONA TRADISIONAL TAMAN NASIONAL SEMBILANG - Turyanto, Erwan; Alamsyah, Zulkifli; Ningsih, Rozaina (JALOW | Journal of Agribusiness and Local Wisdom, 2021)
The traditional zone of the Sembilang National Park has a very important role in sustaining the economy of the fishing community in the Banyuasin II District of Banyuasin Regency. The intended economic activity is a capture fisheries business. This study aims to determine the economic potential of the Sembilang National Park used by fishermen, how the marketing picture occurs, who the marketing institutions are involved in, how the marketing functions are carried out and how efficient they are. The analytical method used in this research is descriptive analysis and margin analysis, profit and cost ratio and farmer's share. The results showed that the economic potential of the Sembilang National Park traditional zone utilized by capture fishermen included 21 species of fish with an economic value of Rp. 13,772,637,732 / month. The traditional zone areas of the Sembilang National Park that are utilized are the Bungin River, Barong River, Sembilang River, Benawang River, Ngirawan River, Birik and Terusan Dalam. Marketing channels are formed in 2 groups, namely: group I type with 5 channels and type II group with 4 channels. The marketing functions performed by marketing institutions include: purchasing, selling, transportation, loading and unloading, preservation, packaging, storage, standardization, risk management, financing, and market information. The results of the marketing efficiency analysis show that in fish marketing group I, channel III is the most efficient channel and channel I is the most inefficient channel. In fish marketing of type II, channel III is the most efficient channel and channel I is the most inefficient channel.